Endophytic fungus Serendipita indica accelerates ascorbate-glutathione cycle of white clover in response to water stress - Rong, Zi-Yi; Jiang, Dao-Ju; Cao, Jin-Li; Hashem, Abeer; Abd_Allah, Elsayed Fathi; Alsayed, Mashail Fahad; Harsonowati, Wiwiek; Wu, Qiang-Sheng (Frontiers in Microbiology, 2022)
Ascorbate-glutathione cycle is an important pathway for plants to scavenge reactive oxygen species under environmental stress conditions. The objective of this study was to investigate the effects of the endophytic fungus Serendipita indica on biomass, chlorophyll concent, reactive oxygen species levels, antioxidant enzyme activities, and ascorbate-glutathione cycle in white clover under ample water and water stress conditions. The results showed that 46 days of soil water stress distinctly promoted root colonization by S. indica. Under water stress, S. indica inoculation significantly promoted shoot and root biomass, total chlorophyll content, and activities of superoxide dismutases (SOD) (e.g., Fe-SOD and Cu/Zn-SOD) and peroxidase in roots, coupled with a decrease in malondialdehyde content in roots. In the ascorbate-glutathione cycle of roots, S. indica also significantly increased the activity of ascorbate peroxidase and glutathione reductase activities in water-stressed white clover, along with the increase in reduced ascorbic acid and reduced/oxidized glutathione contents, thus accelerating the ascorbate-glutathione cycle in inoculated plants to scavenge more reactive oxygen species (e.g., hydrogen peroxide). As a result, S. indica enhanced the tolerance of white clover in response to water stress by enhancing antioxidant enzyme activities and accelerating the ascorbate-glutathione cycle.